PCR Detection, Genotyping, and Differentiation of Toxoplasma gondii from Hammondia hammondi Excreted in the Feces of Cats in Poland Between 2020 and 2024 - Dawid Jańczak; Rafał Stryjek; Aleksandra Kornelia Maj; Jakub Olszewski; Olga Szaluś-Jordanow (Pathogens)
Toxoplasmosis, caused by Toxoplasma gondii, is a widespread parasitic infection affecting humans and animals. The genetic diversity of T. gondii varies across regions, with type I, II, and III strains predominantly circulating in Europe and North America. This study genotyped 67 (78.8%) T. gondii DNA isolates from cats using nested and multilocus PCR-RFLP, identifying type I, genotype #10 (ToxoDB#10), for the first time in Poland. The other 18 (21.2%) stool samples containing T. gondii-like oocysts were confirmed as Hammondia hammondi. Comparative analysis with data from other countries highlights notable regional differences in genotype prevalence. The high occurrence of genotype 3 (ToxoDB#3) in central Europe may be linked to its presence in wild rodents and insectivores, key reservoirs in the parasite’s life cycle. Additionally, genetic analysis of meat products and livestock indicates a potential transmission pathway to felines through raw or undercooked meat consumption. These findings contribute to a better understanding of T. gondii epidemiology and its implications for public health and veterinary medicine.